Rat Sympathetic Neuron Calcium Channels Are Insensitive to Gabapentin - Mallory B. Scott; Paul J. Kammermeier (MDPI AG, 2024)
The gabapentenoids such as gabapentin (GP) and pregabalin are approved for the treatment of chronic pain, but their utility is limited by persistent side effects. These adverse effects result from GPs affecting many types of neurons and muscle cells, not just the pain-sensing neurons that are the intended targets. We have recently discovered a type of peripheral neuron, rat sympathetic neurons from the superior cervical ganglion (SCG), that is uniquely insensitive to GP effects. Currents were measured using whole-cell patch-clamp electrophysiology from cells in primary culture from either the SCG or the Nodose Ganglion (NDG) as a positive control for the effects of GP. We find that the calcium current density was dramatically reduced by GP pretreatment in NDG neurons, but that neurons from the SCG were resistant. Further, when GP was cytoplasmically injected into these neurons, the resistance of SCG neurons to GP treatment persisted. These data demonstrate that rat sympathetic neurons appear to be uniquely resistant to GP treatment. These results may help us to better understand the mechanism of action of, and resistance to, GP in altering calcium channel current density, which may help to develop future treatments with fewer side effects.